Construction land sprawl and reclamation in the Johor River Estuary of Malaysia since 1973. (1st April 2019) - Wang, X.G.; Su, F.Z.; Zhang, J.J.; Cheng, F.; Hu, W.Q.; Ding, Z.
Abstract: The Johor River is the main source of water in Johor Bahru and Singapore as well as a vital maritime passage in the eastern Straits of Johor. However, the Johor River Estuary (JRE) has been experiencing environmental degradation due to construction land sprawl and reclamation (CLSR), which shows a combined effect of anthropogenic environmental change. In this paper, the spatial and temporal variation of CLSR in the JRE was studied based on twelve multi-temporal Landsat images (Landsat MSS, TM and OLI) obtained from 1973 to 2017. The results showed that the area of construction land increased more than 10-fold from 1973 (13.33 km 2 ) to 2017 (135.46 km 2 ). Each type of construction land showed an increasing tendency, and their area-weighted centroids migrated towards the mouth of the Johor River. Over the last four decades, an increased land area of 40.32 km 2 contributed by reclamation was mainly distributed in the Tekong Island and the eastern Singapore Islands, which shortened the minimum distance between lands in the JRE. The largest decrease in minimum distance was 1889 m between Johor Bahru and Tekong Island. CLSR is mainly driven by human activities such as population growth, economic development and policy change. To better protect the coastal environment in the JRE, construction land expansion and reclamation activities should be planned properly by the local government. Highlights: The spatiotemporal variation of construction land sprawl and coastal reclamation in Johor River Estuary had been studied. n.